Quantification of Effects of Fly Ash Type on Concrete Early-Age Cracking - Riding, Kyle A.; Poole, Jonathan L.; Schindler, Anton K.; Juenger, Maria C. G.; Folliard, Kevin J. (My University, 2010)
The mechanisms that contribute to early-age cracking are complex. Determining the relative importance of each mechanism as well as the combined cracking potential for a given concrete material is essential for the concrete industry to construct structures with a long service life. A method for quantifying the cracking risk of a concrete mixture is presented. The method involves testing for the concrete heat of hydration, setting time, free thermal and autogenous movement, restrained stress, and mechanical property development. The concrete uniaxial stress under restrained conditions is measured using a rigid cracking frame. This test setup was used to quantify the effects of using fly ash on the concrete cracking risk using four different fly ashes with varying calcium oxide contents. All fly ashes reduced the cracking risk because of the decrease in the heat of hydration of the cementitious materials and, to a lesser extent, the increased early-age creep.
Keywords: Cracking; Early-age creep; Fly ash; Mass concrete